Immunization coverage and factors associated with immunization status in an urban area of Imphal East district: a cross-sectional study - Thounaojam, Usha D.; Rajkumari, Bishwalata; Chanu, Laishram R.; Kasar, Milachon; Devi, Oinam G.; Ranalcis, Rajkumar; Gairanlung, Thaimei (International Journal Of Community Medicine And Public Health, 2024)
Background: Despite many initiatives undertaken by the government of India, many children remain unvaccinated or under vaccinated, and vaccine preventable diseases are still a leading cause of morbidity and mortality. The present study was done to assess the immunization coverage of children aged 6 to 23 months in an urban area of Imphal East district and to determine the factors associated with immunization gap. We also determined the association of immunization status with some socio-demographic variables. Methods: A cross-sectional study was carried out in all the thirteen villages under urban primary health centre (UPHC), Kshetrigao among mothers or primary caregiver of children aged 6-23 months. Data were collected using semi-structured questionnaires by face to face interview. Results: The total number of respondents was 206. The prevalence of fully immunized, immunized up to date, partial and non immunized were found to be 73%, 59%, 37%, and 3% respectively. Child being sick was the main reason for incomplete immunization. Mother belonging to older age group were found to have significantly higher immunized up to date children than younger mother (p=0.02). Conclusions: The prevalence of immunized up to date children was low. Effective strategy of raising awareness among communities regarding routine vaccination and clarifying their misconceptions related to vaccines is the need of the hour.